Comprehension Level and Parenting Culture with Feeding Behavior of Toddlers in Tulungagung Regency, Indonesia - Wardani, Diadjeng Setya; Chusna, Safira Mauliyatul; Nugroho, Fajar Ari (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Malnutrition in infancy is irreversible on growth and development, so toddlers need adequate and quality food intake. The factors that indirectly cause malnutrition in toddlers are parenting patterns. Mothers’ parenting patterns that are not good in feeding toddlers can be caused by low mothers’ comprehension and behavior in choosing food. This study aims to know comprehension level and parenting culture with the feeding behavior of toddlers in Tulungagung Regency. This study used an analytical observational research design with a cross-sectional study approach. The respondents amounted to 72 mothers of toddlers. The research instrument used a questionnaire and then analyzed using a chi-square test. The majority of mothers with toddlers had good comprehension about nutrition and food intake for toddlers, ideal parenting culture, and adequate feeding behavior. Based on the analysis using chi-square, the comprehension level had a relationship with feeding behavior in toddlers (p-value of 0.013), while parenting culture had no relationship with feeding behavior in toddlers (p-value of 0.270). The conclusion is there is a relationship between the comprehension level and the feeding behavior of toddlers and there is no relationship between parenting culture and the feeding behavior of toddlers.